2021
DOI: 10.3390/rs13112088
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing for Plant Water Content Monitoring: A Review

Abstract: This paper reviews the different remote sensing techniques found in the literature to monitor plant water status, allowing farmers to control the irrigation management and to avoid unnecessary periods of water shortage and a needless waste of valuable water. The scope of this paper covers a broad range of 77 references published between the years 1981 and 2021 and collected from different search web sites, especially Scopus. Among them, 74 references are research papers and the remaining three are review paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 113 publications
(611 reference statements)
1
21
0
Order By: Relevance
“…In other words, the water taken in by the stems increased with the growth stage while that taken in by the leaves decreased throughout the growing seasons. This finding suggested that water storage in stems might play an important role in regulating the plant water status, as suggested by [29,58]. Moreover, all five SVIs showed an obvious dynamic trend of first increasing and then decreasing (Figure 4), which was also reported in another study [59].…”
Section: Linking the Dynamic Variations In Svis With Abiotic And Biotic Factorssupporting
confidence: 76%
See 2 more Smart Citations
“…In other words, the water taken in by the stems increased with the growth stage while that taken in by the leaves decreased throughout the growing seasons. This finding suggested that water storage in stems might play an important role in regulating the plant water status, as suggested by [29,58]. Moreover, all five SVIs showed an obvious dynamic trend of first increasing and then decreasing (Figure 4), which was also reported in another study [59].…”
Section: Linking the Dynamic Variations In Svis With Abiotic And Biotic Factorssupporting
confidence: 76%
“…However, soil moisture may not be the core issue when evaluating drought impacts on agriculture, as a water deficit does not necessarily result in biomass or yield loss [42,65,66]. In fact, in comparison to soil moisture, plant water status is more related to plant physiological functions (e.g., photosynthesis, transpiration, and respiration) [29,67] and is directly connected to biomass and yield production. In addition, leaf water content within a plant canopy plays an important role in light penetration and scattering [68].…”
Section: Impact Mechanism Of the Soil Drying Process On The Svismentioning
confidence: 99%
See 1 more Smart Citation
“…However, the system only uses qualitative data, and withinfield color variations do not allow accurate quantitative estimation of crop parameters. Multispectral sensors are widely adopted for deriving crop vegetation indices (VIs) to predict crop yield [35,36]. However, the system is not able to provide rapid variations that occur in leaf chlorophyll [37].…”
Section: Introductionmentioning
confidence: 99%
“…The functions of these as a medium for metabolic and physiological reactions in plants, in which metabolic and physiological activities can decrease when there is a lack of water and also plays a role as a medium for transporting essential nutrients and minerals from the soil so that a lack of water can reduce the rate of nutrient uptake from the soil by roots [5]. These is also one of the main factors determining plant production related to biomass production and transpiration rate [6]. Water will affect cell turgidity, thereby affecting the process of opening and closing stomata.…”
Section: Introductionmentioning
confidence: 99%